(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Rural areas are neglected, isolated and their literacy level is very low and it is extremely low among women of remote areas. Communication in rural areas in India is a necessary and vital process in achieving the set national goals. This becomes obvious when we consider the fact that nearly 75 per cent of the country’s population houses in more than seven lakh villages. Women constitute 48.5 per cent of the total population, bulk of which reside in rural areas and as many as 80 per cent of which is engaged in agricultural activities. Nowadays, mass media is giving a lot of importance in empowering women by telecasting good programmers and passing information to empower them in social, cultural, economic, educational, legal, decision making, health, technological, equal rights, freedom of expression, gender sensitization areas. The purpose of this study is to analyze how the rapid proliferation and development of mass media is affecting women in rural and remote areas.